Variations in northeast Asian summer precipitation driven by the Atlantic multidecadal oscillation - Si, Dong; Jiang, Dabang; Hu, Aixue; Lang, Xianmei (International journal of climatology, 2021)
By analysing a 113–year (1900–2012) observational dataset, it is shown that the interdecadal fluctuation of the summer precipitation over Northeast Asia differs from that in central East Asia during the 20th century, and has experienced three interdecadal shifts in the 1920s, mid‐1960s and late 1990s. That fluctuation coincides well with the multidecadal fluctuation of the sea surface temperature in the North Atlantic, known as the Atlantic Multidecadal Oscillation (AMO). The AMO affects Northeast Asia via a circumglobal teleconnection pattern extending from the North Atlantic to North America. Corresponding with the positive phase of this teleconnection pattern, a tripolar pattern emerges in the Asian–North Pacific sector, with anomalous low pressure over Northeast Asia and high pressure over Lake Baikal and the mid‐latitude western North Pacific. These results suggest that the positive phase of the AMO favours the occurrence of cold vortex over Northeast Asia and anomalous highs over Lake Baikal and the mid‐latitude western North Pacific in summer, which enhances the East Asian summer monsoon and southward intrusion of high‐latitude cold air, and eventually increases the summer precipitation in Northeast Asia. Furthermore, initialized decadal prediction simulations using the CCSM4 model reproduce well the observed variations of the AMO and its associated atmospheric teleconnection but with slightly shifted geographic locations. The simulated anomalous Northeast Asia cold vortex and strong East Asian summer monsoon, lead to above‐normal summer precipitation over Northeast Asia. The modelling results confirm that the multidecadal variability in the North Atlantic can cause the observed interdecadal variations of Northeast Asia summer precipitation. Our results suggest that to understand and predict interdecadal climate change over Northeast Asia, it is important to consider the key role of the AMO. By analysing a 113‐year observational dataset, it is shown that the interdecadal fluctuation of the summer precipitation over Northeast Asia differs from that in central East Asia during the twentieth century, and has experienced three interdecadal shifts in the 1920s, mid‐1960s and late 1990s. That fluctuation coincides well with the multidecadal fluctuation of AMO. The AMO affects Northeast Asia via a circumglobal teleconnection pattern extending from the North Atlantic to North America.